Food Processing and Preservation - Lajnaf, Roua (IntechOpen, 2023)
Food Processing and Preservation presents both fundamental and applied research on food processing and preservation. It discusses current economic and regulatory policies and their effects on the safety and quality processing and preservation of a wide array of foods. The book explores the latest developments in the field, discusses topics vital to the food industry today, and presents trends in future research and development. Chapters address such topics as thermal and non-thermal food processing, the effect of various food processes on camel milk proteins, techniques like roasting, frying, smoking, and fermentation, the effect of processing on mesquite flour, formulation and edible bigel with the potential to replace trans fats in food products and processing of instant multigrain flakes.